Characteristic of Clorox Poisoning before and during COVID-19 Pandemic, Saudi Arabia, 2019-2020. - Alrougi, Hamoud Marzuq; Sharaheeli, Jaber (American Journal of Health, Medicine and Nursing Practice, 2022)
Purpose: Poisoning is one of the leading causes of morbidities and mortalities worldwide. Due to COVID-19 pandemic, there was a dramatic increase in the use of detergents and disinfectants, both in health care and domestic settings. As Clorox is the most used for these purposes; it was expected that there would be changes in the characteristics of Clorox poisoning. Therefore, the current study aimed to investigate characteristics of Clorox poisoning in Saudi Arabia during Covid-19 pandemic compared to the pre-pandemic period. Methodology: Through a record-based study; all Clorox poisoning cases reported to the ministry of health in 2019 (n=267) representing pre-pandemic and 2020 (n=198) representing during the pandemic periods were collected. The data were retrieved from the electronic database, and it was analyzed using SPSS version 26. Categorical variables are represented as frequency distribution. Finding: There was a decrease in the total number of reported Clorox poisoning cases from 267 pre-pandemic to 198 cases during the pandemic. Females were slightly more than males (55.7% vs 44.3%), and most of the cases were in the age groups (1-5 years) and (20-39 years) (27.3%). The overwhelming majority of the cases occurred at home) (96.3%), with a higher percentage during the pandemic than pre-pandemic (98.0% vs 95.1%), and few minorities occurred intentionally (9.3%). Most of the cases arrived the hospital in stable conditions, with few cases (17.0%) needed antidotes. The great majority of the cases recovered before discharge. The overall incidence of Clorox poisoning reached to 0.57/100,000 population during the pandemic, compared to 0.78/100,000 in the pre-pandemic. Conclusion: There was a decline in incidence of Clorox poisoning during the pandemic; with a relative increase in home incidents, with nausea and vomiting as most common symptoms and all cases recovered. Recommendation: It is highly recommended to plan for a health education messages about safe store and using of detergents and disinfectants.